Synthesis and characterization of putrescine-sulfur analogue/ Adzly H. Sahabudin, Fiona How Ni Foong and Radiah Abdul Ghani - H. Sahabudin, Adzly; Foong, Fiona How Ni; Abdul Ghani, Radiah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Cancer is a disease which has high motility rate worldwide. The current treatment has a high potential to kill cancer cells, however it is lacking of specificity and therefore cause the side effects in normal cells. The alternate pathway has been explored including targeting to cancer cells via polyamine transport system (PTS). The PTS activity is highly upregulated in cancer cells compared to normal cells. In this study, one of the polyamines called putrescine was being exploited to be a vector for sulphur. This putrescinesulphur analogues were synthesized using two different methods. The synthesized product was later characterized using various physicochemical techniques such as gas-chromatography and Fourier transformed-infrared spectroscopy for structural determination. Several putrescine-sulphur analogues was succesfully synthesis with the expected structures